Kontribusi dan efektivitas sektor kelautan dan perikanan terhadap pendapatan asli daerah Provinsi Sulawesi Utara tahun 2022-2025 - Sammy Victor Gabriel Tumbage; Jantje J. Tinangon; Fanda D. P. Rundengan (Yayasan Widyantara Nawasena Raharja, 2026)
North Sulawesi Province possesses substantial marine and fisheries potential, as roughly 73 percent of its territory consists of water. However, this potential has not been matched by a proportional contribution to Regional Original Income (Pendapatan Asli Daerah/PAD). This study analyzes the contribution and effectiveness of the marine and fisheries sector to North Sulawesi Province's PAD for the 2022–2025 period, using a descriptive qualitative case-study approach that combines documentary data with interviews with officials from the Marine and Fisheries Agency. The findings show that the sector's contribution to PAD declined over the period, from 0.12% in 2022 to a low of 0.001% in 2024 before recovering slightly to 0.05% in 2025; in every year the contribution falls into the very-low category, indicating that the sector has not meaningfully supported PAD growth. The effectiveness of revenue management fluctuated more sharply, from very effective (125.86%) in 2022 to not effective (0.85%) in 2024, before improving to fairly effective (88.67%) in 2025, with an average effectiveness of 72.88% across the period, classified as less effective overall. These patterns indicate that revenue targets have not been consistently or optimally achieved, and that target-setting for this sector requires a more conservative, evidence-based approach that better anticipates weather-related and external-demand shocks.